2019
DOI: 10.1128/aem.01741-18
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Biocontrol Agent Pseudomonas pseudoalcaligenes AVO110 to Rosellinia necatrix Exudate

Abstract: Diseases associated with fungal root invasion cause a significant loss of fruit tree production worldwide. The bacterium Pseudomonas pseudoalcaligenes AVO110 controls avocado white root rot disease caused by Rosellinia necatrix by using mechanisms involving competition for nutrients and niches. Here, a functional genomics approach was conducted to identify the bacterial traits involved in the interaction with this fungal pathogen. Our results contribute to a better understanding of the multitrophic interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…Manual curing of COG categories related to cell motility, locomotion, cellular component assembly, and signal transduction (6.8% of the total number of annotated products) revealed that P. alcaligenes AVO110 singletons encode 115 genes related to bacterial lifestyle transitions, such as those involved in flagellar motility, chemotaxis, adhesion, biofilm formation, and colonization of host surfaces, 25 of which encode GDEEF and/or EAL domain proteins (Table S2). We also found that 3 of the 21 P. alcaligenes AVO110 genes previously identified as required for growth in fungal exudates [28] were singletons, i.e., the GGDEF-EAL domain gene cmpA and two genes potentially involved in the metabolism of fatty acids, fadE and fadD.…”
Section: Pan-genome and Core Genome Of P Alcaligenessupporting
confidence: 57%
See 4 more Smart Citations
“…Manual curing of COG categories related to cell motility, locomotion, cellular component assembly, and signal transduction (6.8% of the total number of annotated products) revealed that P. alcaligenes AVO110 singletons encode 115 genes related to bacterial lifestyle transitions, such as those involved in flagellar motility, chemotaxis, adhesion, biofilm formation, and colonization of host surfaces, 25 of which encode GDEEF and/or EAL domain proteins (Table S2). We also found that 3 of the 21 P. alcaligenes AVO110 genes previously identified as required for growth in fungal exudates [28] were singletons, i.e., the GGDEF-EAL domain gene cmpA and two genes potentially involved in the metabolism of fatty acids, fadE and fadD.…”
Section: Pan-genome and Core Genome Of P Alcaligenessupporting
confidence: 57%
“…Pseudomonas and Escherichia coli strains were grown in lysogeny broth (LB) medium [40] or super optimal broth (SOB) [41] at 28 and 37 • C, respectively. BM minimal medium [42] was used for growth of R. necatrix Rn400 mycelia to obtain fungal exudate-containing medium (BM-RE, pH 7.1), as previously described [1,28]. When necessary, solid and liquid media were supplemented with antibiotics as follows: for E. coli, ampicillin (Ap) 100 µg mL −1 , kanamycin (Km) 50 µg mL −1 , and gentamicin (Gm) 50 µg mL −1 final concentration; for P. alcaligenes Microorganisms 2021, 9, 1388 3 of 17 AVO110, Ap 300 µg mL −1 , Km 25 µg mL −1 , and Gm 10 µg mL −1 ; and for P. putida KT2440, Km 50 µg mL −1 and Gm 50 µg mL −1 .…”
Section: Bacterial Strains Media and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations